Acne care in health care providers during the COVID‐19 pandemic: A national survey. Issue 10 (15th August 2022) - Cretu, Stefana; Dascalu, Mihai; Salavastru, Carmen Maria
Abstract: The medical face mask, widely used by health care providers (HCPs) during the COVID‐19 pandemic, is reported to be associated with adverse reactions, among which acne is one of the most common. This study aims to evaluate treatment strategies employed by HCPs affected by acne in association with prolonged medical face mask use, their openness towards accessing telemedicine as a patient, and other lifestyle factors with potential influence on the evolution of their acne. Our online‐based cross‐sectional survey was distributed between December 17, 2020, and February 17, 2021, and targeted HCPs from different medical centers in Romania. From the n =  134 respondents, 50% reported current acne lesions and 56.7% required treatment. Of the latter, 65.8% self‐medicated and 34.2% sought medical advice. The most common treatment associations between anti‐acne topical products were: retinoids and salicylic acid (18.18%; n =  8), retinoids and benzoyl peroxide (13.64%; n =  6), salicylic acid and benzoyl peroxide (13.64%; n =  6), and azelaic acid together with salicylic acid (9.09%; n =  4). The health care provider responders were reluctant to use telemedicine, as only 14.2% participants were open to telemedicine. Our results suggest inadequate management of acne in HCPs using medical face masks. As with other occupational hazards and proper usage of personal protective equipment, HCPs should receive adequate screening, training, and treatment for this condition.